Rethinking Edgar Tekere’s a lifetime of struggle - Gwarinda, Muchineripi Cuthbert (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
This article seeks to interrogate the construction of identities in Edgar Tekeres A Lifetime of Struggle for the purposes of establishing political legitimacy and heroism for himself.This article observers that the autobiographical narrator attempts to achieve this end through constructing heroic identities on a multiplicity of sites such as heredity,military,prisoner,welfare,masculine,intellectual and spiritual identities.The conclusion is that identity is multiple. Heroism is accentuated when that hero identity can be configured into a multiplicity of sub-identities.Hero identities and political legitimacy are achieved in the genre of autobiography through elevating and centering the narrating self while at the same time time undermining the narrated others.It is also achieved through what is stated and the silences.